Banks' Internationalization Strategies: The Role of Bank Capital Regulation - Diemo Dietrich; Uwe Vollmer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2006)
This paper studies how capital requirements influence a bank's mode of entry into foreign financial markets. We develop a model of an internationally operating bank that creates and allocates liquidity across countries and argue that the advantage of multinational banking over offering cross-border financial services depends on the benefit and the cost of intimacy with local markets. The benefit is that it allows to create more liquidity. The cost is that it causes inefficiencies in internal capital markets, on which a multinational bank relies to allocate liquidity across countries. Capital requirements affect this trade-off by influencing the degree of inefficiency in internal capital markets. – – Diese Studie untersucht, wie Eigenkapitalregulierungen die Internationalisierungsstrategien von Banken beeinflussen. Es wird ein Modell einer international operierenden Bank entwickelt, die Liquidität schafft und länderspezifische Liquiditätsschocks ausgleicht. Der Vorteil von Auslandsdirektinvestitionen von Banken gegenüber grenzüberschreitenden Bankdienstleistungen hängt von den Vor- und Nachteilen lokaler Marktkenntnisse ab. Während diese Kenntnisse es erlauben, mehr Liquidität zu schaffen, führen sie zu Ineffizienzen auf internen Kapitalmärkten, auf die eine multinationale Bank angewiesen ist, um die Liquidität zwischen Ländern auszugleichen. Eigenkapitalregulierungen beeinflussen diesen trade-off, indem sie das Ausmaß von Ineffizienzen interner Kapitalmärkte verändern.
urn:nbn:de:gbv:3:2-1309
Keywords: G21; F21; F23; 330; unvollständige Finanzverträge; grenzüberschreitende Finanzdienstleistungen; Auslandsdirektinvestitionen im Bankensektor; Liquiditätsallokation; incomplete financial contracting; cross-border financial services; multinational banking; liquidity allocation; capital regulation